Comparison between metallic and optical interferometric sensors for electromagnetic field measurement (2016)
Many applications around the world use electromagnetic fields (EMF) to accomplish their purposes. Nowadays, to measure these EMF, the use of optical sensors has been rising higher and higher. In this paper, we present a general description of the electromagnetic field optical sensors, more specifically interferometric sensors, with some applications. Also we present a comparison between classical sensors with metallic probes and optical sensors with electro-optical (EO) probes, according to technical parameters showing the advantages of optical sensors beside an economic trend that shows the increase of implementations of this kind of sensors.